(untitled) (Third Sector Social Economic Review, 2025)
In this study, 170 data sets were created from the Ministry of Transport and Infrastructure database for analysis between 2011-2025, including Jan and Feb 2025. In this context, numbers for incoming cruise ships belonging to cruise markets, incoming passengers, outgoing passengers, transit passengers and total number of passengers were created and examined. The average values, minimum and maximum values of these values were analyzed separately on a monthly, annual and port authority basis. The study was done in three stages. In the first stage, status of cruise tourism was expressed statistically. In second stage, time series analysis was performed to determine future estimates. For this purpose, by performing forecast modeling in SPSS 29 package program, estimated values regarding the incoming and outgoing passenger numbers of cruise tourism in Türkiye for next five-year period (2025-2030) are obtained. It is understood that the zero-ship number and zero passenger effect recorded in the statistics during the pandemic period negatively affected forecast the demand. As a result it is observed that negative effect would go on for next 5 years. Finally, estimated values obtained are compared to the values realized in 2024 and comprehensive evaluations for cruise tourism in Türkiye are made.